2018
DOI: 10.1128/mbio.01730-18
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Noncoding RNAs Excised from within Protein-Coding Transcripts

Abstract: Bacteria and archaea utilize regulatory small noncoding RNAs (ncRNAs) to control the expression of specific genetic programs. These ncRNAs are almost exclusively encoded within intergenic regions and are independently transcribed. Here, we report on a large set ncRNAs that are “carved out” from within the protein-coding regions of Escherichia coli mRNAs by cellular RNases. These protected mRNA fragments fold into energetically stable RNA structures, reminiscent of those of intergenic regulatory ncRNAs. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 21 publications
9
65
0
Order By: Relevance
“…Indeed, additional presence of GlmZ* in the assay inhibited GlmZ cleavage when supplied at concentrations of ≥16 nM (Figure 2(b), lanes 7-9). Inhibition of GlmZ cleavage by GlmZ* was less efficient as compared to GlmY, which impeded GlmZ processing already at a concentration of ≥8 nM (Figure 2(b), lanes [10][11][12][13][14]. Taken together, GlmZ* competes with full-length GlmZ for RapZ binding, thereby counteracting GlmZ processing in vitro, but with a somewhat lower efficiency than observed for GlmY.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Indeed, additional presence of GlmZ* in the assay inhibited GlmZ cleavage when supplied at concentrations of ≥16 nM (Figure 2(b), lanes 7-9). Inhibition of GlmZ cleavage by GlmZ* was less efficient as compared to GlmY, which impeded GlmZ processing already at a concentration of ≥8 nM (Figure 2(b), lanes [10][11][12][13][14]. Taken together, GlmZ* competes with full-length GlmZ for RapZ binding, thereby counteracting GlmZ processing in vitro, but with a somewhat lower efficiency than observed for GlmY.…”
Section: Resultsmentioning
confidence: 88%
“…However, RNase E also has important roles for sRNA biogenesis and maturation. Several sRNAs are known to be produced from the 3ʹ region of protein coding genes, either through usage of an internal promoter or by RNase E catalyzed mRNA processing [11][12][13], and regulatory roles for sRNAs generated through the latter mechanism were demonstrated in various species including E. coli and Salmonella [14][15][16][17]. An additional class of sRNAs is autonomously transcribed, but undergoes maturation.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of bacterial sRNAs so far identified are encoded within IGRs and are independently transcribed (Vogel et al ., 2003; Kawano et al ., 2005; Loh et al ., 2009; Chao et al ., 2012; Chao and Vogel, 2016; Dar and Sorek 2018). Nevertheless, a few 3′‐UTR‐derived sRNAs (Kawano et al ., 2005; Kim et al ., 2014; Chao and Vogel, 2016; Chao et al ., 2017; Eisenhardt et al ., 2018; Miyakoshi et al ., 2019), 5′‐UTR‐derived sRNAs (Kawano et al ., 2005; Drecktrah et al ., 2018), and protein coding region‐derived sRNAs (called decay‐generated noncoding RNAs [decRNAs]) (Dar and Sorek, 2018) have been reported in different bacterial species. Surprisingly, our study demonstrated that, in Xcc, mRNA processing is the primary source of cellular sRNA, suggesting a close link between sRNA biogenesis and mRNA decay.…”
Section: Discussionmentioning
confidence: 99%
“…These can be transcribed from promoters internal to the coding sequence or cleaved from the longer mRNA. There also are hints of sRNAs being derived from 5′ UTRs (11,20) and possibly even from within coding sequences (90). To generate the specific small transcript in these cases, there need to be promoters, terminators, or ribonuclease cleavage sites internal or adjacent to the coding sequence.…”
Section: Regulation Of Srna Levels and Activitymentioning
confidence: 99%